Flow State: Menaklukan Hal Mustahil? - M. Haeru Anwar; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this research is to find out Haeru Anwar's perspective from the 1 Hari Success Youtube channel entitled